ESTUDO COMPARATIVO DO PROCESSO DE AVALIAÇÃO DA EFETIVIDADE DE P&D NUMA EMPRESA BRASILEIRA DE ENERGIA - Santos, Edson Feitosa dos (2012)
This research aims to carry out a critical analysis of R&D effectiveness evaluation process at the Research Center of Petrobras. Firstly, seeking evidence of alignment of this process with the assumptions of the company's strategy for R&D. Secondly, by comparing the model used in the organization to assess the R&D effectiveness with frameworks found in the literature. Through a case study, quali-quantitative in nature, the research provided some conclusions, including: (1) that the absence of use of some indicators of strategic themes didn't matter in detachment between the corporate and technological strategies; (2) that the systematic work R&D portfolio balancing, through a structure of committees could ensure the strategic alignment of R&D Function and, (3) that although evidence signs of maturity, the framework used in the organization, can incorporate improvements arising from the R&D effectiveness assessment frameworks covered in this comparative study. As a suggestion for future work it´s recommended repeating this study in a larger sample of companies and checking the effectiveness of the use of structures of committees in the balancing of R&D portfolios in other types of organizations, with the purpose to avoid the Strategic Dissonance.